The human cytotoxic T cell response to influenza A vaccination. - Mcmichael, A; Gotch, F; Cullen, P; Askonas, B; Webster, R (1981)
The human cytotoxic T lymphocyte (CTL) response to challenge with influenza A vaccine was studied. Six of eight volunteers given killed whole influenza virus A/USSR (H1N1) vaccine showed substantial increases on the level of CTL memory 1 month after immunization. The CTL measured at this time showed complete cross-reactivity in their specificity for influenza A/USSR (H1N1) and A/X31 (H3N2) infected cells and also showed HLA restriction. The level of CTL memory increased in only three out of nine donors given subunit vaccine and showed no change in those not given vaccine. If cytotoxic T cells are important in influenza prophylaxis, killed whole virus vaccine should offer better protection than subunit vaccine.